The Socio-Technical Background of an Unconventional Software Architecture in OpenStreetMap: Understanding the Implementation of ‘Folksonomy - Glasze, Georg; Plennert, Matthias; Schlieder, Christoph (Computational Culture, 2019)
Previous software studies have stressed the socio-technical origin and embeddedness of software; hence specific socio-technical contexts are always inscribed into the digital structure. Inspired by the observation that the software architecture in OpenStreetMap (OSM) differs fundamentally from well-established conventions in the geospatial field, namely using folksonomies as an attribution system, this paper exposes and records the digital remains of the software development process within this successful, open and voluntary geodata project. We aim to reveal the socio-technical background of this software feature by analyzing digital archives of communication and coding in OSM with a combination of qualitative and quantitative methods. Thus we trace this specific feature through the entire processes of technological and social negotiations as well as the implementation. Our findings show that there were several competing technologies within the project; the final decision towards one of them was based on a do-ocracy — those who do the coding work get to decide how it’s done - and thus independently from discussions on the main communication medium: the OSM mailing list. We argue that the communication on the mailing list conceals the de-facto oligarchic environment of technological decision-making: contributors without the necessary technical skills for participating in the software development are only allegedly able to get involved in discussions regarding the technological orientation of OSM.
Keywords: OpenStreetMap; Volunteered Geographic Information; Software Studies; Digital Geography